Innovation Strategy in Business : Increasing Efficiency and Competitiveness in the Digital Age - Arief Prayitno (Jurnal Ekonomi, Akuntasi dan manajemen Indonesia (JEAMI), 2023)
In the digital era, innovation in business become factor key in increase efficiency operational and power competition company. Research This aiming For analyze the innovation strategies implemented in business as well as the impact to efficiency work and excellence competitive. The research method used is approach qualitative with technique studies literature and interviews deep to practitioner business in various sector industry. Research results This show that implementation of innovation strategy business in a way effective can increase Power competitiveness and efficiency operational company. Investment in proven research and development (R&D) play a role in create more products and services innovative, while collaboration with partner external accelerate the process of innovation and adoption technology new. In addition, the approach based on customers and improvements experience customer through digitalization service contribute to improvement satisfaction and loyalty customers. The implementation of prototyping and testing has also proven reduce risk failure products on the market, while innovation sustainable (green innovation) not only increase image company, but also provides benefit economy through efficiency source power. In overall, results study This confirm that innovation business is factor key in reach superiority competitive, adaptation to market changes, and growth companies in the digital era.